2009
DOI: 10.1007/s00296-009-1288-6
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against oxidized low-density lipoprotein and lipid profile in patients with chronic periaortitis: case–control study

Abstract: Objective: Chronic periaortitis is thought to result from an autoallergic reaction to oxidized low-density lipoprotein (OxLDL). No data exist on lipid profile and atherosclerotic biomarkers. We investigated circulating levels of OxLDL and of anti-OxLDL (aOxLDL) antibodies in patients with chronic periaortitis. Conclusion: Data suggest a differing innate immune response to OxLDL in patients with chronic periaortitis compared to controls. Whether this response is causally related to chronic periaortitis devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…It might be worth noting that elderly males are most frequently affected by IRF, as with IgG4-related disease and atherosclerosis. This has led to the hypothesis originally formulated by Mitchinson and Parums [12,13] that an inflammatory stimulus deriving from atherosclerotic plaques, which are associated with ageing and more frequent in men, would lead in predisposed individuals to an autoimmune reaction to plaque-related antigens eventually followed by fibrosis [14]. These aspects will be expanded upon in the paragraph regarding the pathogenesis of IRF.…”
Section: E P I D E M I O L O G Ymentioning
confidence: 96%
“…It might be worth noting that elderly males are most frequently affected by IRF, as with IgG4-related disease and atherosclerosis. This has led to the hypothesis originally formulated by Mitchinson and Parums [12,13] that an inflammatory stimulus deriving from atherosclerotic plaques, which are associated with ageing and more frequent in men, would lead in predisposed individuals to an autoimmune reaction to plaque-related antigens eventually followed by fibrosis [14]. These aspects will be expanded upon in the paragraph regarding the pathogenesis of IRF.…”
Section: E P I D E M I O L O G Ymentioning
confidence: 96%
“…Also, chronic periaortitis may affect patients without atherosclerosis, and it has been reported in pediatric patients (Miller et al, 2003). A recent study showed no significant differences in anti-ox-LDL antibody levels between patients with chronic periaortitis and controls (van Bommel et al, 2011). Furthermore, a number of findings support the hypothesis that chronic periaortitis may be a manifestation of systemic disease rather than the result of a local reaction.…”
Section: Pathogenesismentioning
confidence: 82%
“…In a recent study, van Bommel et al [32 ]showed no significant difference between patients with stable chronic periaortitis and control subjects with regard to oxLDL Ab titers. Our study population consisted of patients with AA dilatation due to AR or hypertension, and none of the patients had AAA.…”
Section: Discussionmentioning
confidence: 98%